Factors Influencing Smoking Habits Among Adolescents in Tegal Rejo Village, Medan Perjuangan District - Nurhayati, Talitha Syafira; Aidha, Zuhrina; Wasiyem, Wasiyem (Journal La Medihealtico, 2024)
Smoking behavior among adolescents is a particular issue that requires serious attention. Adolescents tend to be more vulnerable to the influence of their surroundings, including peers and social media, which can affect their decisions regarding smoking. This study aims to explore the factors related to smoking behavior among adolescents in Indonesia. Using quantitative methods, univariate and bivariate analyses were conducted on data from 271 respondents. The findings indicate a significant relationship between individual knowledge about the dangers of smoking, individual attitudes toward smoking, social media exposure to content about the dangers of smoking, and the level of self-efficacy with smoking behavior among adolescents. These results support the importance of understanding and managing these factors in efforts to prevent and control smoking among adolescents. Strategies that include enhancing knowledge, supportive attitudes, managing social media exposure, and strengthening self-efficacy can be effective steps in reducing the prevalence of smoking behavior in the adolescent population. In this context, evidence-based approaches, such as those proposed by Lawrence Green's Theory of Behavior Change, can serve as a foundation for designing more effective interventions. Collaboration among various parties, including the government, educational institutions, and the general community, is necessary to create a supportive environment to change smoking behavior and improve adolescent health overall.